Motivasi Kerja Terhadap Kinerja Karyawan pada PT Dagsap Endure Eatore Jakarta Selatan - Julia Retnowulan; Isnurrini Hidayat Susilowati; Wiwik Widiyanti (Cakrawala - Jurnal Humaniora, 2019)
Human resources is one important factor for the progress of a company, one of the aspects that affect the achievement of human resources that have high performance is the motivation of work. The purpose of this study to determine the effect of work motivation on employee performance at PT Dagsap Endura Eatore Jakarta. The author uses the method of observation, questionnaires, study documentation. The author distributed questionnaires to 56 respondents by using Likert scale. Data analysis technique using correlation coefficient, determination, regression equation, then writer process the data by using SPSS version 22. Based on calculation of correlation coefficient obtained equal to 0,750 which mean, there is strong relation between work motivation to employee performance at PT Dagsap Endura Eatore Jakarta. From result of calculation of coefficient of determination obtained result of equal to 0,563 or 56% and the rest 44% influenced by other factors like compensation, promotion, training, and seen from regression equation formed Y = 14,774 + 0,650X this indicate that without work motivation employee performance of 14,774 units and if the motivation to work increased 1 unit it will increase the employee performance of 0.650 units.